Agaricus bisporus and its in vitro culture as a source of indole compounds released into artificial digestive juices - Muszyńska, Bożena; Kała, Katarzyna; Sułkowska-Ziaja, Katarzyna; Krakowska, Agata; Opoka, Włodzimierz (Food chemistry, 2016)
•Rate of the release of indole compounds was determined from Agaricus bisporus.•Release of indole compounds to artificial digestive juice was observed.•l-Tryptophan, 5-hydroxy-l-tryptophan, melatonin, 5-methyl-tryptamine, tryptamina, 6-methyl-d,l-trytophan were found.•Serotonin was determined only in gastric juice. The popularity of Agaricus bisporus results not only from the quality of the flavors, but also from the content of many substances of therapeutic properties. This paper presents a study on RP-HPLC determination of the content of indole compounds released from the lyophilized biomass from in vitro cultures of A. bisporus into artificial digestive juices at 37°C. A. bisporus in vitro cultures were grown on media enriched with zinc salts. The release of 5-hydroxy-l-tryptophan and l-tryptophan was found in the greatest number of samples. The content of 5-hydroxy-l-tryptophan in the investigated samples ranged from 86.62 to 531mg/100g d.w. The amount of l-tryptophan was determined within the range of 1.63–4.68mg/100g d.w. and for melatonin 0.43–0.64mg/100g d.w. It was demonstrated for the first time that in vitro cultures of A. bisporus release indole compounds in conditions simulating the human digestive tract.